Forget a mentor, find a sponsor : the new way to fast-track your career - Hewlett, Sylvia Ann, 1946- (Boston, Massachusetts : Harvard Business Review Press, 2013)
Who's pulling for you? Who's got your back? Who's putting your hat in the ring? Odds are this person is not a mentor but a sponsor. Mentors can build your self-esteem and provide a sounding board--but they're not your ticket to the top. If you're interested in fast-tracking your career, what you need is a sponsor--a senior-level champion who believes in your potential and is willing to advocate for you as you pursue that next raise or promotion.
Why sponsorship? -- How sponsorship works -- Embrace your dream and do a diagnostic -- Scan the horizon for potential sponsors -- Distribute your risk -- Understand that it's not all about you -- Come through on two obvious fronts -- Deliver a distinct personal brand -- Lead with a yes -- Sex -- Distrust -- Executive presence -- Epilogue : castles.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Career development; Mentoring in business; Success in business; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Reference; BUSINESS & ECONOMICS / Skills; elektronické knihy; electronic books